PENGGUNAAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Yeremia, Firmanus; Sugiyono, Sugiyono; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is whether the use of video learning can improve IPS outcomes of students in grade IV SD Negeri 02 Segiring? "The purpose of this study was to describe the improvement in the results of social studies of students in grade IV  of SD Negeri 02 Segiring by using learning videos". The method used is descriptive method with a form of classroom action research and is collaborative. The place of research took place at Segiring 02 State Elementary School, the research subjects were class teachers and fourth grade students. Data collection techniques used are direct observation and document observation techniques with data collection tools namely IPKG 1 sheet and IPKG 2 sheet sheet as well as student learning outcomes documents. The study was carried out in 3 cycles, namely in the first cycle which was 2.79 with enough categories, the second cycle 3.37 with good categories and the second cycle increased to 3.83 categorized very well. The implementation of learning from the first cycle is 2.67 with sufficient categories, in the second cycle increased to 3.49 in the good category and in the second cycle at 3.94 in the excellent category. The average student in the first cycle was 60.31, in the second cycle increased to 72.54 and in the third cycle was 81.46. Based on the data obtained, it can be concluded that there is an increase in each cycle. Thus, research using video learning in improving student learning outcomes in class IV SDN 02 Segiring. Keywords:    Using, Video Learning, Study Result